Working towards inclusive and equitable trauma treatment guidelines: a child-centered reflection. Issue 1 (31st December 2020) - Alisic, Eva; Roth, Jessica; Cobham, Vanessa; Conroy, Rowena; De Young, Alexandra; Hafstad, Gertrud; Hecker, Tobias; Hiller, Rachel; Kassam-Adams, Nancy; Lai, Betty; Landolt, Markus; Marsac, Meghan; et al.
ABSTRACT: Clinical practice guidelines, such as those focusing on traumatic stress treatment, can play an important role in promoting inclusion and equity. Based on a review of 14 international trauma treatment guidance documents that explicitly mentioned children, we reflect on two areas in which these guidelines can become more inclusive and equitable; a) representation of children's cultural background and b) children's opportunity to have their voice heard. While a few guidelines mentioned that treatment should be tailored to children's cultural needs, there was little guidance on how this could be done. Moreover, there still appears to be a strong white Western lens across all stages of producing and evaluating the international evidence base. The available documentation also suggested that no young people under the age of 18 had been consulted in the guideline development processes. To contribute to inclusion and equity, we suggest five elements for future national guideline development endeavours. Promoting research and guideline development with, by, and for currently under-represented communities should be a high priority for our field. Our national, regional and global professional associations are in an excellent position to (continue to) stimulate conversation and action in this domain.